Relationship Between Personal Protective Equipment Use and Contact Dermatitis in Palm Oil Pesticide Workers - Waren, Annes; Ayuningtiyas, Ratih; Wahyuda, Aradana (KnE Life Sciences, 2021)
Contact dermatitis is the most common occupation-related dermatological disease. Skin contact with chemicals that are irritants or allergens continuously cause vulnerability in workers. Among the chemicals that can cause contact dermatitis are pesticides, which are often used in the community, particularly by palm oil plantation companies. The use of personal protective equipment (PPE) is one risk control for contact dermatitis. This study aimed to determine the relationship between PPE usage and contact dermatitis among palm oil plantation workers who dispense pesticides. Using a cross-sectional research design and a total sampling technique, the study analysed data on contact dermatitis obtained from workers’ medical records and PPE usage through random observations for three days. The results showed that 62.2% of pesticide workers had experienced contact dermatitis within the past three months, and there was a significant relationship between insufficient PPE usage and contact dermatitis (p-value < 0.001). Therefore, the occurrence of contact dermatitis can be reduced by increasing PPE usage. Keywords: contact dermatitis, pesticide, personal protective equipment, palm oil